Redundant manipulators kinematics inversion - Yahya, S.; Moghavvemi, M.; Mohamed, H.A.F. (Academic Journals., 2011)
A robotic system is kinematically redundant when it possesses more degrees of freedom than those required to execute a given task. This paper reviews the well-known methods used to find the inverse kinematics of redundant manipulators. Because redundant manipulators have infinite solutions for their inverse kinematics, therefore the conventional method that was used to calculate the inverse kinematics of non-redundant manipulators cannot be used. The methods used to calculate the inverse kinematics of redundant manipulators are divided into three main categories in this paper: pseudoinverse, artificial intelligence and geometrical methods. These types have been explained, their advantages and disadvantages are also discussed in this paper.